Aesthetics exploration of chiaroscuro light: capturing the visual atmosphere of traditional markets in Jakarta - Aziz, Abdul; Tobroni, M Imam (Institut Seni Indonesia Surakarta, 2023)
Photography is needed as a medium of expression and delivery of communication messages. In the field of art, Chiaroscuro is a new vehicle for expression to be translated as a visual object in creating street photography. The main focus that is interesting to know is about the aesthetics of chiaroscuro light in the art of photography. The purpose of this research is to describe how to visualize the aesthetic expressions of researchers about traditional markets in the area of Jakarta. The research method employs an artistic approach within the context of visual field research, emphasizing creativity, subjective perspectives, and interpretations. The analysis techniques center on formal aspects of visual elements, including composition, color, shape, line, and texture, with the goal of understanding how these elements contribute to the overall aesthetic and communicative qualities of the image. Photographic exposure and description are supported by subjective observations. The results of the study show that photography is able to provide aesthetic expression according to the wishes of the researcher. The research contributes to the field by exploring the use of chiaroscuro as a novel expressive tool in street photography, particularly in the context of traditional markets in Jakarta. It demonstrates how an artistic approach and formal visual analysis techniques can effectively capture and convey the aesthetic qualities of these markets, ultimately resulting in a tangible outcome in the form of a photo book, enriching our understanding of urban culture and visual communication.